Factors influencing participation in screening and clinical trials - Asch, Rachel E. (Cranfield University, 1988)
The reported research was an investigation of attitudes and beliefs associated with participation in screening programmes and clinical trials, carried out by general practitioners. Particular focus was given to cardiovascular risk-reduction. The work comprised two main studies. The preliminary study was entirely exploratory, designed to guage public attitudes towards GP involvement with preventive screening programmes and clinical research; and to identify the range of variables associated with participation in such projects. The subsequent study utilised a more formal approach in which the Behavioural Intention Model was utilised to evaluate the power of influencing factors. Both studies employed self-completion questionnaires, developed from preliminary in-depth interview data. For the first study instrument distribution was effected by personal approach, for the second study postal distribution was employed. In all, 1,037 respondents contributed to the surveys - 442 to the preliminary exploration and 695 to the follow-on study. These represented response rates of approximately 65% and 36% respectively. The main findings were that attitudes towards screening were generally favourable, though there was less conformity in attitudes expressed towards clinical trials. These findings were reflected in reported participatory intentions. No evidence was found of any factors which might pose widespread barr i ers to screen ing part ic i pa t ion, though some potent ia 1 deterren ts were identified for older women. It was also noted that other potential deterrents may have been masked by the 'middle class' bias of the sample. Major deterrents to trial entry were identified as worries about: sideeffects, acquired resistance, discontinuation of current effective medications and lack of adequate information. These all interacted with the 'guinea pig' factor. Response rates and responses associated with medical and non-medical sampling sources were also discussed; and consideration was made of the general utility of the Behavioural Intention Model for research of this kind.